Novel, heterozygous, de novo pathogenic variant (c.4963delA: p.Thr1656Glnfs*42) of the NF1 gene in a Chinese family with neurofibromatosis type 1 - Lisha Yang; Jiewen Fu; Jingliang Cheng; Baixu Zhou; Maomei Chen; Songyot Anuchapreeda; Junjiang Fu (BMC, 2023)
Abstract Neurofibromatosis type 1 (NF1) presents an autosomal dominant, haploinsufficient, and multisystemic disorder with patches of skin café-au-lait spots, lisch nodules in the iris, even tumors in the peripheral nervous system or fibromatous skin. In this study, a Chinese young woman who suffered from NF1 disease with first-trimester spontaneous abortion was recruited. Analysis for whole exome sequencing (WES), Sanger sequencing, short tandem repeat (STR), and co-segregation was carried out. As results, a novel, heterozygous, de novo pathogenic variant (c.4963delA:p.Thr1656Glnfs*42) of the NF1 gene in the proband was identified. This pathogenic variant of the NF1 gene produced a truncated protein that lost more than one-third of the NF1 protein at the C-terminus including half of the CRAL-TRIO lipid-binding domain and nuclear localization signal (NLS), thus leading to pathogenicity (ACMG criteria: PVS1 + PM2 + PM2). Analysis for NF1 conservation in species revealed high conservation in different species. Analysis of NF1 mRNA levels in different human tissues showed low tissue specificity, which may affect multiple organs presenting other symptoms or phenotypes. Moreover, prenatal NF1 gene diagnosis showed both alleles as wild types. Thus, this NF1 novel variant probably underlays the NF1 pathogenesis in this pedigree, which would help for the diagnosis, genetic counseling, and clinical management of this disorder.